Analisis Skala Prioritas Pengendalian Banjir di Kabupaten Kubu Raya - Nauli, Sachika Aurelia; Soeryamassoeka, Stefanus Barlian; Umar, Umar (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Geographical conditions and a suboptimal drainage system capacity make Kubu Raya Regency in West Kalimantan Province highly vulnerable to flooding. This study aims to determine the priority scale in flood control in three subdistricts, including Sungai Raya, Sungai Ambawang, and Kuala Mandor B, by using the Analytical Hierarchy Process (AHP) method. Data were collected by distributing questionnaires to stakeholders and related parties to obtain paired assessments of various criteria and alternative strategies. The analysis results show that the most effective priority strategies for each region are a reforestation program in Sungai Raya District, the implementation of flood-prone area zoning in Sungai Ambawang, and a revision of spatial planning policies in Kuala Mandor B. These findings are expected to provide an empirical basis for the local government in formulating effective flood mitigation policies.